GAMBARAN MAKNA HIDUP PADA PSK REMAJA YANG MENJALANI REHABILITAS DI PSKW ANDAM DEWI SOLOK - Zhafran Ezra Akbar; Nurmina (CAUSALITA : Journal of Psychology, 2024)
Prostitution in adolescents is already very worrying because of the many cases of exploitation of adolescents. Adolescent prostitutes who undergo rehabilitation because they are arrested by the Civil Service Police Unit (Satpol PP) will be a source of pressure on their lives, especially if the perpetrators of prostitution are teenagers, they tend to be more vulnerable to experiencing various negative emotional and psychological impacts due to punishment such as guilt, loss of freedom, feelings of shame, economic sanctions and will affect physical adjustment but also individual psychology. This study aims to look at the description of the meaning of life in adolescent prostitutes undergoing rehabilitation at PSKW Andam Dewi Solok. This research uses a phenomenological approach with qualitative methods. Data collection was carried out using semi-structured interview techniques with 2 (two) subjects who were teenage prostitutes undergoing rehabilitation at PSKW Andam Dewi Solok. The data analysis technique in this study used the Interpretative Phenomenological Analysis (IPA) technique. The results of this study found that the subject of teenage prostitutes who are undergoing rehabilitation can achieve 5 (five) stages in finding the meaning of life proposed by Bastaman. Then, the factors that influence the meaning of life in this study are self-understanding, positive behavior, relationship intimacy, deepening the chess of values, and worship.